Judicial Protection for Sharia Consumers: A Normative Analysis of OJK Regulation No. 2 of 2024 and the Competence of Religious Courts - Ahmad Syauqi Azmi Ramadhan; Surya Sukti; Baihaki; Mualimin (Justitia Jurnal Hukum, 2026)
Strengthening Sharia governance through Financial Services Authority Regulation (POJK) No. 2 of 2024 is pivotal for enhancing Sharia compliance and consumer protection. However, a significant gap remains between institutional governance and the practical enforcement of consumer rights. This article analyzes this disparity by evaluating POJK No. 2/2024 within the framework of Sharia economic law and the judicial role of Religious Courts. Using a normative-juridical method with statutory and conceptual approaches, this study finds that POJK No. 2/2024 remains focused on administrative-institutional realms, failing to optimally integrate with the Financial Sector Development and Strengthening Law (PPSK Law) and the adjudicatory authority of Religious Courts. To address this, this article develops a judicial-normative model that positions POJK No. 2/2024 as a "standard of care" in Sharia consumer dispute adjudication. This model transcends mere administrative compliance by transforming OJK’s governance standards into enforceable legal benchmarks for judges to determine professional negligence and liability. By integrating maqāṣid al-sharī’ah with access to justice, this research repositioning the Religious Court not merely as a dispute resolver, but as a strategic enforcer of Sharia-compliant consumer protection standards.